2002
DOI: 10.1210/jc.2002-020871
|View full text |Cite
|
Sign up to set email alerts
|

High Circulating Ghrelin: A Potential Cause for Hyperphagia and Obesity in Prader-Willi Syndrome

Abstract: Prader-Willi syndrome (PWS) is a genetic disorder occurring in 1 of 10,000-16,000 live births and is characterized by excessive appetite with progressive massive obesity as well as short stature and mental retardation. Most patients have GH deficiency and hypogonadotropic hypogonadism. The causes of the hyperphagia and abnormal GH secretion are unknown. To determine whether ghrelin, a novel GH secretagogue with orexigenic properties, is elevated in PWS, we measured fasting plasma ghrelin concentration; body co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
196
2
7

Year Published

2002
2002
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 318 publications
(215 citation statements)
references
References 28 publications
10
196
2
7
Order By: Relevance
“…The present study confirms previous reports (DelParigi et al, 2002, Haqq et al, 2003, Goldstone et al, 2004and Tauber et al, 2004) that fasting and postprandial ghrelin levels are significantly higher in PWS subjects compared to obese and lean subjects. However, in contrast to previous reports , Goldstone et al, 2004, Goldstone et al, 2005and McLaughlin et al, 2004, our data suggest that the observed increase in ghrelin in PWS is not due to altered fat distribution or hypoinsulinemia because PWS and obese subjects were matched for total and central adiposity and showed similar insulin secretion and insulin resistance.…”
Section: Discussionsupporting
confidence: 93%
“…The present study confirms previous reports (DelParigi et al, 2002, Haqq et al, 2003, Goldstone et al, 2004and Tauber et al, 2004) that fasting and postprandial ghrelin levels are significantly higher in PWS subjects compared to obese and lean subjects. However, in contrast to previous reports , Goldstone et al, 2004, Goldstone et al, 2005and McLaughlin et al, 2004, our data suggest that the observed increase in ghrelin in PWS is not due to altered fat distribution or hypoinsulinemia because PWS and obese subjects were matched for total and central adiposity and showed similar insulin secretion and insulin resistance.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast to the imaging results, the blood plasma levels of glucose, insulin, ghrelin and PYY were found in accordance with the predictions: levels of all of the above were significantly different between the fasting and high-energy meal conditions. While ghrelin levels were elevated in comparison to controls in previously published literature, 35,[41][42][43] recent work has shown that even when ghrelin levels are reduced to a normal level, using somatostatin or a somatostatin agonist, there is no effect on appetite or food intake in individuals with PWS. 44,45 This suggests that the dysfunction in PWS is central in origin, rather than as a result of abnormalities in the periphery, at least in terms of the measures in this study.…”
Section: Discussionmentioning
confidence: 71%
“…[8][9][10][11][12] Ghrelin is a potent circulating orexigenic hormone that is produced mainly in the stomach. Circulating ghrelin levels rise after fasting and are suppressed by food intake.…”
Section: Hypogonadismmentioning
confidence: 99%